A JOURNEY TOWARDS ECONOMIC WELLBEING BY EMPOWERING WOMEN THROUGH MICROFINANCE - Debnath, Priyanka; Mishra, Archana (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This study examines how microfinance interventions impact political, social, psychological, and economic empowerment and disempowerment. Disempowerment in the political, social, psychological, and economic spheres sometimes results in prejudice against women in society. As a result, the microfinance scheme for those living in rural areas emerged, concentrating on women as agents of social change. Consequently, several research that used a very broad definition of women empowerment and were published in journals with peer review were left out. To eliminate any uncertainty in the theoretical and empirical foundation, this study's examination of women's empowerment through microfinance is grounded in a comprehensive literature survey. A thorough literature review forms the basis of this study's analysis of women's empowerment via microfinance to ensure completeness in the empirical and theoretical underpinnings. According to the literature, finance as an example has not brought about the necessary socio-economic transformation and has even had negative effects in certain circumstances. However, this study demonstrates that the program for microfinance empowers women and lessens societal inequities to some level.